2022
DOI: 10.1038/s41536-022-00253-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-specific hydrogels for growth factor-free vasculogenesis

Abstract: Integrin-binding biomaterials have been extensively evaluated for their capacity to enable de novo formation of capillary-like structures/vessels, ultimately supporting neovascularization in vivo. Yet, the role of integrins as vascular initiators in engineered materials is still not well understood. Here, we show that αvβ3 integrin-specific 3D matrices were able to retain PECAM1+ cells from the stromal vascular fraction (SVF) of adipose tissue, triggering vasculogenesis in vitro in the absence of extrinsic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…However, the assembly of a vasculature demands complex physiological process to occur not only between cells and matrix but cells and neighboring cells. EC outgrowth begins with integrin binding with matrix and proceeds with cell-to-cell interplay both in vasculogenesis and angiogenesis [65][66][67] . To understand the role of matrix plasticity in EC outgrowth, a tailored hydrogel system is required that can decouple mechanical plasticity from other physical properties (e.g., stiffness), and also allows the physiological process of vasculature formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the assembly of a vasculature demands complex physiological process to occur not only between cells and matrix but cells and neighboring cells. EC outgrowth begins with integrin binding with matrix and proceeds with cell-to-cell interplay both in vasculogenesis and angiogenesis [65][66][67] . To understand the role of matrix plasticity in EC outgrowth, a tailored hydrogel system is required that can decouple mechanical plasticity from other physical properties (e.g., stiffness), and also allows the physiological process of vasculature formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, its clinical translation has been highly hampered by an insufficient number required for therapy. We previously shown that SVF cells respond to integrin-specific 3D matrices triggering vasculogenesis in vitro in the absence of extrinsic growth factors [ 31 ]. Moreover, we provided evidence that this pre-vascularization in vitro benefits the engraftment of the constructs indicating that this strategy can be an alternative to other similar strategies that rely on cells with limited availability.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work we demonstrated a benefit in tissue neovascularization with integrin-specific biomaterials pre-vascularized by SVF cells capable of triggering vasculogenesis in the absence of extrinsic growth factors [ 31 ]. Herein, we hypothesized that an in vitro prevascularization stage would accelerate the healing cascade by fostering the early vascularization of the wound by inosculating with the host vasculature, further potentiating the effect of SVF.…”
Section: Introductionmentioning
confidence: 99%
“…Applying this principle, our group has proposed the use of the stromal vascular fraction (SVF) of adipose tissue as a self-directing system to obtain microvasculature in TE constructs. [16][17][18] The SVF is a cellular fraction that can be isolated from fat and is composed of diverse cell populations, including endothelial and stromal cells, [19] that when seeded and left to grow, spontaneously self-assemble into a lumenized capillary bed-like network (Figure 2B). This process requires neither additional supportive cell populations, nor potentially harmful extrinsic growth factors.…”
Section: Doi: 101002/adbi202300291mentioning
confidence: 99%